Maximum Noble-Metal Efficiency in Catalytic Materials: Atomically Dispersed Surface Platinum - Bruix, Albert; Lykhach, Yaroslava; Matolinova, Iva; Neitzel, Armin; Skala, Tomas; Tsud, Nataliya; Vorokhta, Mykhailo; Stetsovych, Vitalii; Sevcikova, Klara; Myslivecek, Josef; Fiala, Roman; Vaclavu, Michal; et al. (Angewandte Chemie International Edition, 2014)
Platinum is the most versatile element in catalysis, but it is rare and its high price limits large-scale applications, for example in fuel-cell technology. Still, conventional catalysts use only a small fraction of the Pt content, that is, those atoms located at the catalyst's surface. To maximize the noble-metal efficiency, the precious metal should be atomically dispersed and exclusively located within the outermost surface layer of the material. Such atomically dispersed Pt surface species can indeed be prepared with exceptionally high stability. Using DFT calculations we identify a specific structural element, a ceria "nanopocket", which binds Pt2+ so strongly that it withstands sintering and bulk diffusion. On model catalysts we experimentally confirm the theoretically predicted stability, and on real Pt-CeO2 nanocomposites showing high Pt efficiency in fuel-cell catalysis we also identify these anchoring sites.
Keywords: ceria nanoparticles; density functional calculations; heterogeneous catalysis; model catalyst; platinum